Relasi Eksekutif dalam Penyelenggaraan Otonomi Daerah di Takalar - Asrizal, Andi; Hasran, Hasran; Rahman, Rahman (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Muhammadiyah Sinjai, 2023)
This study aims to determine the relationship between the executive and the legislature in relation to the role of the Takalar Regency DPRD in the 2019-2024 period, and to find out the functions carried out by the Takalar Regency DPRD in the 2019-2024 period within the framework of regional autonomy. The type of research used is qualitative with a phenomenological approach. The results of the research show that the relationship between the executive and the legislature in relation to the role of the Takalar Regency DPRD in the 2019-2024 period is as stipulated in laws and regulations, especially in Law Number 23 of 2014 concerning Regional Government. In this connection there is actually nothing special or prominent in carrying out their respective government functions. Both the DPRD and the Takalar Regency government have their respective duties, authorities and obligations in accordance with statutory regulations. There are also no special or specific roles and functions carried out by the DPRD of Takalar Regency for the 2019-2014 period within the framework of regional autonomy, everything goes according to the existing mechanisms as specified in laws and regulations, especially Law Number 23 of 2014 concerning Regional Government. The roles and functions of the DPRD as specified in statutory regulations, namely the supervisory function, the legislative function and the budget function, in addition, the DPRD as the people's representative functions to carry out the functions of the people's representatives, one of which is conveying the aspirations of the people in terms of welfare.